Trade Labor, Market Rigidities, and Government-Financed Technological Change - Winfried Koeniger (Institute for the Study of Labor (IZA), 2001)
This paper contributes to the debate on the effects of trade versus technological change on wage differentials. We propose an explanation of the stylized facts which is based on interactions between openness and technological change because of labor market institutions and government intervention. In particular, technology change is induced by rigid wage elements for a developed economy which is trading with less developed countries. With a binding minimum wage and given commodity prices, openness induces the government to subsidize technological innovation in the developed country because production activities in the sector hit by foreign competition would have to close down otherwise. The economy with a binding minimum wage and institutionally induced innovations differs from the flexible economy in the following way: ? The wage differential becomes more compressed the higher the minimum wage. Not only the wage of the unskilled is higher, but also the wage of the skilled is lower. ? The productivity of unskilled workers is higher in the sector intensive in its use. ? Skill intensity within the unskilled-labor intensive sector can rise although the wage of the skilled rises as well. This perspective may explain why empirical studies have difficulties to find substantial effects of openness on wage differentials although product markets have become increasingly integrated. Moreover, it can explain why the volume of trade between developed and less-developed countries is relatively small. Finally our model yields predictions for developed countries with different labor market institutions that are consistent with empirical evidence.
Keywords: F1; F4; J3; O3; 330; Trade; government; minimum wage; technology change; Lohnstruktur; Facharbeiter; Ungelernte Arbeitskräfte; Faktorproportionentheorem; Außenwirtschaft; Internationaler Wettbewerb; Technischer Fortschritt; Arbeitskosten; Forschungssubvention; Nord-Süd-Beziehungen; Theorie; OECD-Staaten